Dithiocarbamate Complexes of Platinum Group Metals: Structural Aspects and Applications - Yee Seng Tan; Chien Ing Yeo; Edward R. T. Tiekink; Peter J. Heard (Inorganics, 2021)
The incorporation of dithiocarbamate ligands in the preparation of metal complexes is largely prompted by the versatility of this molecule. Fascinating coordination chemistry can be obtained from the study of such metal complexes ranging from their preparation, the solid-state properties, solution behavior as well as their applications as bioactive materials and luminescent compounds, to name a few. In this overview, the dithiocarbamate complexes of platinum-group elements form the focus of the discussion. The structural aspects of these complexes will be discussed based upon the intriguing findings obtained from their solid- (crystallographic) and solution-state (NMR) studies. At the end of this review, the applications of platinum-group metal complexes will be discussed.